Fostering scientific inquiry and STEM skills in higher education: A Ukrainian case study - Dmytro V. Lubko (CTE Workshop Proceedings)
This paper presents a case study of the scientific activities and STEM education initiatives implemented at the Department of Computer Sciences at Dmytro Motornyi Tavria State Agrotechnological University in Ukraine. The study examines how engaging students in research projects, scientific circles, and STEM-focused curricula can enhance their acquisition of technical skills, problem-solving abilities, and overall academic performance. Findings suggest that participation in these activities fosters a sense of responsibility, creativity, and teamwork among students while preparing them for successful careers in their chosen fields. The paper discusses the key components of the department's approach, including intelligent systems projects, robotics workshops, and industry collaborations, as well as the challenges and opportunities encountered in the implementation process. Recommendations are provided for adapting and scaling similar initiatives in other higher education contexts. The study underscores the importance of integrating scientific inquiry and STEM education into the undergraduate experience to cultivate a new generation of skilled and innovative professionals.